Federal Energy Administration regulation : report of the Presidential task force - United States; MacAvoy, Paul W. (Washington : American Enterprise Institute for Public Policy Research, 1977)
This text provides analytical studies on regulatory reform. It examines FEA regulation of the petroleum industry, concluding that the cost of the current regulatory programme outweigh its benefits.
kjo 16/01/2019
Loans
Keywords: Petroleum industry and trade; Industrial policy